Low temperature electrical transport in modified carbon nanotube fibres. (September 2015) - Lekawa-Raus, Agnieszka; Walczak, Kamil; Kozlowski, Gregory; Hopkins, Simon C.; Wozniak, Mariusz; Glowacki, Bartek A.; Koziol, Krzysztof
Graphical abstract: Abstract : Carbon nanotube fibres are a new class of materials highly promising for many electrical/electronic applications. The range of applications could be extended through the modification of their electrical transport properties by inclusions of foreign materials. However, the changes in electrical transport are often difficult to assess. Here, we propose that the analysis of resistance–temperature dependencies of modified fibres supported by a recently developed theoretical model may aid research in this area and accelerate real life applications of the fibres.